A Nursing Management Model to Increase Medication Adherence and Nutritional Status of Patients with Pulmonary TB - Eka Mishbahatul Mar’ah Has (Jurnal Ners, 2015)
Introduction: High dropout rate, inadequate treatment, and resistance to medication, still become an obstacle in the treatment of pulmonary TB. Pulmonary TB patient care management at home can be done actively through telenursing. N-SMSI (Ners-Short Message Service Intervention) is one of community nursing intervention, in which community nurses send short messages to remind patients to take medication and nutrition. The aim of this study was to analyze the effect of nursing management model N-SMSI to increased medication adherence and nutritional status of patients with pulmonary TB.Methods: This study was used prospective design. The populations were new pulmonary TB patient at intensive phase, at Puskesmas Pegirian Surabaya. Samples were taken by purposive sampling technique; consist of 30 people, divided into treatment and control groups. The independent variable was N-SMSI. The dependent variables were medication adherence collected by using questionnaire and nutritional status by using measurement of body weight (kg). The data were then analyzed by using Wilcoxon Signed Rank Test, Mann Whitney, and Independent t-test with α ≤ 0.05.Results: The results of wilcoxon signed rank test had showed difference in the nutritional status of the treatment group before and after intervention, with p = 0.001. It’s similar with the control group, with p = 0.002. Mann whitney test results had showed no signifi cant difference in nutritional status between treatment and control group, as indicated by the value of p=0.589. While independent t-test had showed difference in compliance between treatment and control group, with p=0.031.Conslusion: N-SMSI can improve medication adherence of patient with Pulmonary TB. This model can be developed by nurse as alternative methods to improve medication adherence in patients with Pulmonary TB. Further research should modify nursing management model which can improve the nutritional status of patient with Pulmonary TB.